A New Perspective on Sustainable Soil Remediation—Case Study Suggests Novel Fungal Genera Could Facilitate in situ Biodegradation of Hazardous Contaminants. Issue 2 (2nd March 2016) - Czaplicki, Lauren M.; Cooper, Ellen; Ferguson, P. Lee; Stapleton, Heather M.; Vilgalys, Rytas; Gunsch, Claudia K.
Abstract : Deciding upon a cost effective and sustainable method to address soil pollution is a challenge for many remedial project managers. High pressure to quickly achieve cleanup goals pushes for energy‐intensive remedies that rapidly address the contaminants of concern with established technologies, often leaving little room for research and development especially for slower treatment technologies, such as bioremediation, for the more heavily polluted sites. In this case study, new genomic approaches have been leveraged to assess fungal biostimulation potential in soils polluted with particularly persistent hydrophobic contaminants. This new approach provides insights into the genetic functions available at a given site in a way never before possible. In particular, this article presents a case study where next‐generation sequencing has been used to categorize fungi in soils from the Atlantic Wood Industries Superfund site in Portsmouth, Virginia. Data suggest that original attempts to harness fungi for bioremediation may have focused on fungal genera poorly suited to survive under heavily polluted site conditions, and that more targeted approaches relying on native indigenous fungi which are better equipped to survive under site‐specific conditions may be more appropriate. ©2016 Wiley Periodicals, Inc.